'n Ondersoek na die tydruimtelike aspek in Voetskrif van Breyten Breytenbach - Conradie, Pieter Jacques Jan (Afrikaans and Netherlandic Studies, 2016)
Voetskrif was written in 1975 while the poet Breyten Breytenbach was awaiting trial in Pretoria. The anthology itself was published in 1976 and reflects the poet's seclusion in space and time. As such, the theme of exile once again comes to the fore in the work of this Afrikaans poet. Estranged from all immediate contact with the outside world, the poet looks inwards. In order to fill the void, he relies on his memory to conceptualize a world in terms of a reality of words. The exploration of space-time is done through the medium of imagination. Dreams and memories must suffice to reach beyond the boundaries of imprisonment. The poet's imagination also enables him to "mark time". He needs to breathe in death's house - the prison - and this is done by manipulating the word. The absence of time in the prison is transformed into the timelessness of thought as the poet strives through one poem after the other, to adapt himself and alleviate his distress. Each poem can be seen as an interlude delaying the flow of time. The typography of the poems may suggest that the lyric moment abolishes time. However, Breytenbach's existence in time and space cannot be ignored and the "here and now" always refers to the prison-cell. The use of the Zen-Buddhistic concept of time and the "here and now" may convey a sense of apathy to the Western mind, yet the poet is clearly preoccupied with time and space.